The impact of heterogeneity of variances on the genetic evaluation of performance traits in Nellore cattle - de Menezes, Flávio Luiz; de Araújo, Cláudio Vieira; Novo, Larissa Carolina; Laureano, Monyka Marianna Massolini; Araújo, Simone Inoe; Lôbo, Raysildo Barbosa; de Castro, Letícia Mendes; Nakabashi, Lílian Roberta Matimoto; Baldi, Fernando [UNESP] (Revista Brasileira de Zootecnia, 2022)
The objective was to evaluate the existence of heterogeneity of variances and its impact on the genetic evaluation of ponderal performance in sires of the Nellore breed. We used records of adjusted body weights at 210 (W210), 365 (W365), and 450 (W450) days of age. Both W365 and W450 were combined by principal component analyses using the first component (PC). Average daily gain (ADG) was obtained by difference between W450 and W210. The classes of standard deviations (SD) for W210, PC, and ADG were obtained by the standardization of means of herd-year means subclasses, with positive values composing the high SD and values equal and less than zero composing the SD. The model included the fixed effects of contemporary group and age at calving as a covariate, random genetic additive, and maternal genetic (except for PC) effects, and the permanent maternal environment. Variance components were obtained by Gibbs sampling. Posterior means of heritability in analyses without considering heterogeneity of variances ranged from 0.15±0.01 to 0.31±0.01. Posterior means of genetic correlations between the two classes of SD for W210, PC, and ADG were equal to 0.85±0.04, 0.83±0.03, and 0.71±0.08, respectively. Spearman correlation to breeding values of sires for ADG as the selection intensity increased in them, and the correlations between breeding values in general analyses were more correlated with those predicted in the high DP. Therefore, when there is a higher selection intensity on the sires only for the ADG criterion, there is a significant presence of the heterogeneity of variances and impact on the genetic evaluation of the sires. Thus, for ADG, the predictions of breeding values obtained by the genetic evaluation model in which the heterogeneity of variances are not considered are more weighted by the class of greater heterogeneity.
Keywords: Animal breeding; Beef cattle; Genetic correlation; Heritability